Molecular phylogeny and divergence time estimates of Penaeid Shrimp Lineages (Decapoda: Penaeidae) - Voloch, Carolina M; Freire, Pablo R; Russo, Claudia A M (Zootaxa, 2009)
Fossil record of penaeids indicates that the family exists since the Triassic period, but extant genera appeared only recently in Tertiary strata. Molecular based divergence time estimates on the matter of penaeid radiation were never properly addressed, due to shortcomings of the global molecular clock assumptions. Here, we studied the diversification patterns of the family, uncovering, more specifically, a correlation between fossil and extant Penaeid fauna. For this, we have used a Bayesian framework that does not assume a global clock. Our results suggest that Penaeid genera originated between 20 million years ago and 43 million years ago, much earlier than expected by previous molecular studies. Altogether, these results promptly discard late Tertiary or even Quaternary hypotheses that presumed a major glaciations influence on the diversification patterns of the family.